Pengaruh penambahan sari temulawak (Curcuma xanthorrhiza Roxb.) terhadap kadar asam lemak bebas (FFA), pH dan kadar kurkumin pada telur asin - Kurniawan, Muflihuda Agiel; Thohari, Imam; Radiati, Lilik Eka (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2015)
The purpose of this research was to investigate the quality and the best concentration of curcuma juice on salted egg. The method of this research was experimental research with Completely Randomized Design using 4 treatments and 4 replications. The curcuma juice were divided into P0 (0%), P1 (25%), P2 (50%) and P3 (75%). The variables were free fatty acids, pH and levels of curcumin. The data were analyzed by Analysis of Variance continued by Honestly Significant Difference test method by Tukey if there were sigificant differences among variables. The results of this research showed that the addition of curcuma juice 75% could improve the quality of salted eggs, reduced levels of free fatty acids (0.37%) and increased levels of curcumin salted egg (0.657 ppm). The addition of  curcuma juice couldn’t improve the quality of salted egg which was indicated by increased pH of albumin 7.94. The addition of curcuma juice indicated  similar result to the control treatment (P0) which was indicated pH of yolk  6.55. Keywords: functional food, curcuma juice concentration